Influence of Tooth Profile Parameter of Double-circle-arc Flexspline on Conjugate Characteristic of Harmonic Gear Drive - Anfu Yuan; Shengfeng Qiu; Xukai Shi (Jixie chuandong)
Abstract In the process of harmonic drive（HD），the double-circular-arc tooth profile（DCTP） can effectively avoid cusp meshing. In order to further optimize the double arc profile and improve the performance of the HD，based on the modified kinematic method exact conjugate theory，and using Matlab programming calculation，the influence and laws of the main parameters in the flexspline profile（FSP） on the conjugate zone and conjugate tooth profile are compared and analyzed. The results show that the convex tooth profile radius，concave tooth profile radius and radial deformation amount of FSP have significant influence on the shape of conjugate tooth profile. The obliquity and length of common tangent have significant influence on the conjugate zone and arc length of conjugate tooth profile. Reasonable selection of flexspline profile parameters can effectively improve the transmission performance of harmonic gear device.